Crossing the Ocean by Feeling for the BITs: Investor-State Arbitration in China’s Bilateral Investment Treaties - Irwin, Amos (2012)
Although China began to sign bilateral investment treaties (BITs) in the 1970s, it refused to grant foreign investors the right to sue their host government in international arbitration tribunals. Few realize that China’s treaty negotiators have in fact abandoned this restriction in almost every Chinese BIT signed since 1998, including those with Latin America. Scholars have suggested that China reversed its policy in order to support Chinese overseas investors or to fit its general economic liberalization strategy. However, China’s BITs with Mexico, Peru, and Colombia as well as its arbitration case with Peru contradict these theories. I argue that China began signing open BITs to test the risks of granting open access to European countries and the United States, for whom open access is a key condition. China experimented gradually with open arbitration, just as it has experimented gradually with many economic changes since Reform and Opening began in 1978. This theory has interesting implicationsfor China’s future BITs—as international arbitration tribunals threaten to make this experiment permanent, China has added new restrictions that bring China’s BITs closer to the US model and make a US-China BIT more likely. However, the US avoids BITs with capital-exporting countries, and China is now a large capital-exporter. The main obstacle to US-China BIT negotiations may no longer be the two nations’ differences, but rather their similarities.